\(\left(x-4\right)\left(x+4\right)=0\Leftrightarrow\left[{}\begin{matrix}x=4\\x=-4\end{matrix}\right.\)
x^2-16=0
<=> x^2 = 16
<=>x = √16
<=> x = 4 hoặc x = -4
x2 - 16 = x2 - 42 = (x - 4)(x + 4) = 0
=> x = 4 hoặc x =–4
(x = +–4)
\(\left(x-4\right)\left(x+4\right)=0\Leftrightarrow\left[{}\begin{matrix}x=4\\x=-4\end{matrix}\right.\)
x^2-16=0
<=> x^2 = 16
<=>x = √16
<=> x = 4 hoặc x = -4
x2 - 16 = x2 - 42 = (x - 4)(x + 4) = 0
=> x = 4 hoặc x =–4
(x = +–4)
Tìm \(x\)
a, \(x^2-10x+25=0\)
b, \(x^2-8x+16=0\)
c, \(x^2-49=0\)
d, \(4x^2-25=0\)
Tìm x biết: a)x(x-3)+x-3=0 b)(5x-4)^2-16^2=0
Tìm x biết:
a/ 5x( x- 3) = x – 3 b/ x3 - x = 0 c/ x2 – 7x + 6 = 0
d/ x2 – 4 + ( x – 2)2 = 0 e/ x2 – 16 –( x +4) = 0 f/ x2 + x – 2 = 0
BT2: Tìm x 2, 3x(x-4)+2x-8=0 3, 4x(x-3)+x^2-9=0 4, x(x-1)-x^2+3x=0 5, x(2x-1)-2x^2+5x=16
tìm x biết: x+2/10+ x+2/13+ x+2/16+ x+2/19 =0
biết 2/3 x(x^2 -16) =0,các số x tìm được là
Tìm x biết: (x-3)^2-16=0
x^2 -2x=24
(2x+1)+(x+3)^2(x+7)(x-7)=0
(x+4)^2-16=0 tìm x
tìm x
(x+4)2- (x+1)(x-1)= 16
(2x-1)2+ (x+3)2- 5(x+7)(x-7)=0